THE EFFECT OF ADDING LIMNOCHARIS POWDER (Limnocharis flava) ON THE CATFISH (Pangasius hypopthalmus) ABON QUALITY - Dipo Dwi Prakoso; Dewita Buchari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study aims to determine the influence of the addition of powder limnocharis to the quality of sherdded catfish. The method used is experimenting with Design Random Complete (DRC) non factorial, as the treatment is powder limnocharis which consists of four of which are: A0 without the addition of powder limnocharis, of the A1 with the addition of powder limnocharis 20 grams, A2 with the addition of powder limnocharis 40 grams and A3 by the addition of powder limnocharis 60 grams. Parameters that is organoleptic and chemical. The result showed that the best of the quality of sherdded is the addition of powder limnocharis 20 grams. The organoleptic with the criteria like chocolate green; the smells of sherdded catfish and spices is strong; the typical sherdded catfish; the texture of tiny fibers and soft. The chemical with a value of the water content of 4.48 %, protein content 29.40 % and levels of fiber 2.75 %.Key words: fish abon, limnocharis powder, catfish, increasing